Polyol synthesis of Mn3+ substituted Fe3O4 nanoparticles: Cation distribution, structural and electrical properties. (September 2015) - Amir, Md.; Ünal, B.; Shirsath, Sagar E.; Geleri, M.; Sertkol, M.; Baykal, A.
Highlights: Mn 3+ substituted Fe3 O4 (Mn x Fe2−x O4 ) NPs were synthesized by polyol method. The effect of Mn 3+ substitution on the structural and dielectric properties of Fe3 O4 was studied. Fe 3+ ions have both tetrahedral and ochedral site preferences. Abstract: In this study, Mn x Fe2 − x O4 ( x  = 0.0, 0.2, 0.4, 0.6, 0.8 and 1.0) nanoparticles were synthesized by polyol route and the effect of Mn 3+ substitution on structural and dielectric properties of Fe3 O4 was studied. X-ray powder diffraction (XRD) patterns confirmed the single spinel ferrite phase formation (Rietveld analysis). Crystallite size of the synthesized materials lie in the range of 12–25 nm as calculated X-ray diffraction patterns using Scherrer's formula. The microstructural features were examined by SEM images. Cation distribution calculations confirmed Fe 3+ ions have both tetrahedral and ochedral site preferences whereas Mn 3+ ions mostly occupies tetrahedral A-site. The ac electrical and dielectric properties of Mn 3+ ion substituted Fe3 O4 nanoparticle show that there were significant changes in both conductivity and complex permittivity as well as dielectric loss tangent as Mn 3+ ion concentration is varied from zero to unity. It is clearly seen that conductivity increases with increase in temperature which may be due to increase in hopping capability of charge carriers at higher temperatures. Detailed evaluation of analysis reveals that at higher frequencies there is less effect of temperature on conductivity which can be interpreted on the basis of interfacial, dipolar, ionic and electronic polarization as detailed above section in explanation of variation of dielectric loss. The dielectric permittivity shows dielectric behavior can be clarified on the basis of Koop's interpretations in accordance with two layer Maxwell–Wagner model by accounting for surface charges. The electrical and dielectric properties, i.e. ac/dc conductivity, real/complex dielectric permittivity, and dielectric loss (tan δ ) decrease with Mn 3+ ion doping in some aspects.